2014
DOI: 10.1111/1460-6984.12118
|View full text |Cite
|
Sign up to set email alerts
|

Swahili speech development: preliminary normative data from typically developing pre‐school children in Tanzania

Abstract: The study contributes a preliminary set of normative data on speech development of Swahili-speaking children. Findings are discussed in relation to theories of phonological development, and may be used as a basis for further normative studies with larger numbers of children and ultimately the development of a contextually relevant assessment of the phonology of Swahili-speaking children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
24
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 20 publications
5
24
1
Order By: Relevance
“…Building on this single case, Naidoo et al (2005) analysed phoneme acquisition, syllable structure and phonological processes in 18 isiZulu-speaking children aged between 3;0 and 6;2 using the children's naturalistic speech samples. Naidoo et al (2005) suggested that vowels develop before the age of 3;0 in isiZulu, similar to the Bantu languages of Kiswahili (described by Gangji, Pascoe & Smouse, 2015); Setswana (Mahura & Pascoe, 2016) and isiXhosa (Maphalala, Pascoe & Smouse, 2014). The isiZulu-speaking children between the ages of 3;0 and 4;0 had complete inventories of nasals, plosives and approximants.…”
Section: Introductionmentioning
confidence: 71%
See 4 more Smart Citations
“…Building on this single case, Naidoo et al (2005) analysed phoneme acquisition, syllable structure and phonological processes in 18 isiZulu-speaking children aged between 3;0 and 6;2 using the children's naturalistic speech samples. Naidoo et al (2005) suggested that vowels develop before the age of 3;0 in isiZulu, similar to the Bantu languages of Kiswahili (described by Gangji, Pascoe & Smouse, 2015); Setswana (Mahura & Pascoe, 2016) and isiXhosa (Maphalala, Pascoe & Smouse, 2014). The isiZulu-speaking children between the ages of 3;0 and 4;0 had complete inventories of nasals, plosives and approximants.…”
Section: Introductionmentioning
confidence: 71%
“…The studies by Maphalala et al (2014) on isiXhosa, Gangji et al (2015) on Kiswahili, and Mahura and Pascoe (2016) on Setswana are similar in terms of sample size (24 -36 participants). These studies developed and used picture-naming assessments to collect data.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations